A contribution to adequate use of freshwater sponges as a proxy in paleoenvironmental studies - Docio, L.; Parolin, M.; Pinheiro, U. (Zootaxa, 2021)
This paper provides a comprehensive review of the environments where freshwater sponges occur and evaluates the use of sponge spicules as a proxy in paleoenvironmental studies in the Neotropical region. The paper aims to: I) review the information about the ecology of inland sponges to facilitate the use of spicules as a paleoenvironmental tool; and II) identify possible incongruities in the use of this information in paleoenvironmental reconstructions that have been conducted in Neotropical regions. The study compiled data on 77 sponge species, specialist or generalist that occur under certain environmental conditions, such as: substrate type for growth, hydrodynamic types, as well as salinity and acidity concentrations. In addition, it provides a comparison of the paleoenvironmental conditions applied to reconstruction studies that have been carried out within this biogeographic region, highlighting incongruities regarding the current ecology of the sponges.